Bicyclic Pyrrolidine-Isoxazoline γ Amino Acid: A Constrained Scaffold for Stabilizing α-Turn Conformation in Isolated Peptides - Oliva, Francesco; Bucci, Raffaella; Tamborini, Lucia; Pieraccini, Stefano; Pinto, Andrea; Pellegrino, Sara (Frontiers in Chemistry, 2019)
Unnatural amino acids have tremendously expanded the folding possibilities of peptides and peptide mimics. While alpha,alpha-disubstituted and β-amino acids are widely studied, γ-derivatives have been less exploited. Here is reported the conformational study on the bicyclic unnatural γ amino acid, 4,5,6,6a-tetrahydro-3aH-pyrrolo[3,4-d]isoxazole-3-carboxylic acid 1. In model peptides, the (+)-(3aR6aS)-enantiomer is able to stabilize alpha-turn conformation when associated to glycine, as showed by 1H-NMR, and circular dichroism experiments, and molecular modelling studies. alpha-Turn is a structural motif occurring in many biologically active protein sites, although its stabilization on isolated peptides is quite uncommon. Our results make the unnatural γ-amino acid 1 of particular interest for the development of bioactive peptidomimetics.